The impact of the comorbid seizure/epilepsy on the health related quality of life in people with multiple sclerosis: an international multicentric study - Drulovic, Jelena; Pekmezovic, Tatjana; Tamas, Olivera; Adamec, Ivan; Aleksic, Dejan; Andabaka, Marko; Basic Kes, Vanja; Butkovic Soldo, Silva; Cukic, Mirjana; Despinic, Livija; Dincic, Evica; Djelilovic Vranic, Jasminka; et al. (Frontiers in Immunology, 2023)
The health-related quality of life (HRQoL) of people with (Pw) multiple sclerosis (MS) is usually deteriorated. It has been recently suggested that comorbidities may have the negative influence on the quality of life of the PwMS, but according to the best of our knowledge, only one study investigated, although in a very small cohort, the impact of individual comorbidity on the quality of life of PwMS. The aim of our investigation was to assess, in an international, multicentric study, the impact of comorbid seizure/epilepsy on the HRQoL in PwMS. We conducted cross-sectional study at numerous neurological centers in Serbia, Croatia, Bulgaria, Montenegro, Northern Macedonia, and Bosnia and Herzegovina (Federation of Bosnia and Herzegovina and Republic of Srpska). For each patient, demographic and clinical data were collected, including Expanded disability status scale (EDSS) score. Beck Depression Inventory (BDI) and the 36-Item Short Form Health Survey (SF-36) questionnaires were administered to all patients. The study comprised 326 PwMS in total, 127 PwMS with seizure/epilepsy and 209 PwMS without. Both mean Physical health composite (PHC) and mental health composite (MHC) scores, were statistically significantly higher in PwMS without seizure/epilepsy, implicating worse quality of life in PwMS with comorbid seizure/epilepsy. Presence of seizure/epilepsy in pwMS was statistically significant independent predictor of both PHC and MHC, in multivariate linear regression model after adjustment for potential confounding variables. The hierarchical multivatiate regression analysis was performed in order to establish the most important predictors of the PHC and MHC of the SF-36, in PwMS with seizure/epilepsy; older age, higher level of disability, as measured by EDSS, higher depression score, drug-resistant epilepsy and shorter time since last seizure were found to significantly predict worse MHC score in PwMS with seizure/epilepsy. Our results point to the possible role of the interventions related to the adequate control of epilepsy along with improvement of the mental health status to be important in order to reduce MS burden in the PwMS with comorbid seizure/epilepsy.